Sulphate resistance of lightweight aggregate concrete comprising sieved palm oil fuel ash as fine aggregate replacement - Khairunisa, Muthusamy; Saffuan, Wan Ahmad; Mohd Hanafi, Hashim; Nabilla, Mohamad; Kırgız, Mehmet Serkan; Muhammad Aimran Amzar, Kamarudin; Ravindran, Gobinath (Elsevier Ltd, 2022)
Oil palm shell (OPS) and palm oil fuel ash (POFA) disposal from palm oil industry causes environmental pollution. The present research investigates the compressive strength and sulphate resistance of oil palm shell lightweight aggregate concrete containing palm oil fuel ash as partial fine aggregate replacement. Sieved POFA was used as partial fine aggregate replacement from 0% up to 20% by weight of sand. Water cured specimens were tested to determine compressive strength and durability towards sulphate attack. Use of 10% POFA slightly enhances concrete strength and durability against sulphate attack via pozzolanic reaction from the fraction of fine ash present.